2019
DOI: 10.1002/jts.22404
|View full text |Cite
|
Sign up to set email alerts
|

Associations Among Exposure to Potentially Morally Injurious Experiences, Spiritual Injury, and Alcohol Use Among Combat Veterans

Abstract: Potentially morally injurious experiences (PMIEs) are events that may violate deeply held values or belief systems. Combat engagement places service members at a heightened risk for PMIE exposure. Exposure to PMIEs may elicit internal conflict between moral beliefs and experiences and, if unresolved, conflict may manifest as feelings of guilt, shame, and spiritual or existential crisis. Further, distress caused by these experiences may promote harmful behaviors (e.g., excessive alcohol use), which may serve as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 65 publications
(111 reference statements)
3
25
1
Order By: Relevance
“…Tellingly, these were veterans for whom spirituality or religion was an important personal value, thus suggesting the need for further investigations to take into account the wide diversity of belief systems that might shape the meaning given and the consequences accruing from morally injurious events. The subsequent paper continues this theme, with Battles, Kelley, Jinkerson, Hamrick, & Hollis’ () investigation of the associations among PMIEs, spiritual injury (defined as alienation from or anger at one's deity), and the specific outcome of problematic alcohol use among combat veterans. Intriguingly, spiritual injury mediated the effects of MI on alcohol use for men but not for women in the sample, suggesting the importance for future research to examine potentially gender‐specific forms of maladaptive coping with the negative aftermath of MI.…”
Section: The Present Special Issuementioning
confidence: 89%
“…Tellingly, these were veterans for whom spirituality or religion was an important personal value, thus suggesting the need for further investigations to take into account the wide diversity of belief systems that might shape the meaning given and the consequences accruing from morally injurious events. The subsequent paper continues this theme, with Battles, Kelley, Jinkerson, Hamrick, & Hollis’ () investigation of the associations among PMIEs, spiritual injury (defined as alienation from or anger at one's deity), and the specific outcome of problematic alcohol use among combat veterans. Intriguingly, spiritual injury mediated the effects of MI on alcohol use for men but not for women in the sample, suggesting the importance for future research to examine potentially gender‐specific forms of maladaptive coping with the negative aftermath of MI.…”
Section: The Present Special Issuementioning
confidence: 89%
“…Whereas earlier reports emphasized the detrimental effects of MI on previously held beliefs about morality, goodness of people, and self (Jinkerson, ; Litz et al., ), recent work has suggested that exposure to PMIEs may further impact spiritual and religious foundations (Battles et al., ; Yeterian et al., [this issue]). Battles and colleagues () reported that spiritual injury, together with exposure to PMIEs, mediates the association between combat exposure and alcohol use among male veterans. In another study, Currier, Foster, et al.…”
Section: Outcomes Of Moral Injurymentioning
confidence: 94%
“…Previous research 48 has found that military reserve or active service status to be protective of psychological wellbeing due to higher levels of social support compared to military veterans who have left service. However, two studies did not find a consistently significant association between active or reserve status 49 and fewer PMIEs or moral injury-related mental health symptoms as compared to military veterans (see Table 6). Taken together, our result found the role of social support in moral injury development is not entirely clear and, as all of these studies included military samples, how social support influences moral injury in other contexts remains unknown.…”
Section: Pmie and Psychosocial Or Demographic Factorsmentioning
confidence: 97%
“…Ames et al 37 further clarified this relationship by observing a significant positive association for religious struggles and loss of religious faith or hope and suicidality following PMIEs in U.S. military veterans. Battles et al 38 demonstrated that both higher levels of exposure to PMIEs and experiences of spiritual injury were significantly associated with increased alcohol use after combat exposure (see Table 5). However, this relationship was only significant for male veterans (data not shown in table) and could represent a gender-specific maladaptive coping mechanism to manage the negative emotions caused by spiritual injuries.…”
Section: Religiosity and Spiritualitymentioning
confidence: 99%